Incidence of cerebral vasospasm after endovascular treatment of acutely ruptured aneurysms - Murayama, Yuichi (1997)
Cerebral vasospasm is the most common cause of morbidity and mortality in patients admitted to the hospital after suffering aneurysmal subarachnoid hemorrhage (SAH). The early surgical removal of subarachnoid clots and irrigation of the basal cisterns have been reported to reduce the incidence of vasospasm. In contrast to surgery, the endovascular treatment of aneurysms does not allow removal of subarachnoid clots. In this study the authors measured the incidence of symptomatic vasospasm after early endovascular treatment of acutely ruptured aneurysms with Guglielmi detachable coils (GDCs). Sixty-nine patients classified as Hunt and Hess Grades I to III underwent occlusion of intracranial aneurysms via GDCs within 72 hours of rupture. The amount of blood on the initial computerized tomography (CT) scan was classified by means of Fisher's scale. Symptomatic vasospasm was defined as the onset of neurological deterioration verified with angiographic or transcranial Doppler studies. Hypertensive, hypervolemic, hemodilution therapy, with or without intracranial angioplasty, was used to treat vasospasm after GDC placement. Symptomatic vasospasm occurred in 16 (23%) of 69 patients. The clinical grade at admission and the amount of blood on the initial CT were both associated with the incidence of subsequent vasospasm. At 6-month clinical follow-up examination, 12 of these 16 patients experienced a good recovery, two were moderately disabled, and two patients had died of vasospasm. In conclusion, the 23% incidence of symptomatic vasospasm in this series compares favorably with that found in conventional surgical series of patients with acute aneurysmal SAH. These results indicate that endovascular therapy does not have an unfavorable impact on cerebral vasospasm.